Progress report from the AMAP Board to the SAO Meeting in Yakutsk, Russia April 6-7, 2005. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Council Secretariat, 2005)
Arctic Council working group Arctic Monitoring and Assessment Programme (AMAP)s report to SAOs at the Arctic Council Senior Arctic Officials meeting in Yakutsk, Russia, April 6-7 2005.